ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS VIII DALAM MENYELESAIKAN SOAL CERITA SPLDV - Indriani Fitrianingsih; Indra Budiman (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
This study aims to analyze the mathematical problem solving ability of class VIII students in solving problems regarding the Two Variable Linear Equation System (SPLDV). The basis of this research is the weak mathematical problem solving ability of junior high school students. The subjects of this study were 5 students of class VIII SMP from Bogor Regency. The approach used in this research is a qualitative approach with a descriptive method. This study uses a test tool to see the students' ability to solve mathematical problems in story problems using the Two Variable Linear Equation System (SPLDV) material. The data analysis technique used in this research is qualitative data analysis. Judging from the results of the analysis, some students still cannot solve the questions according to Polya's steps. From the results of research on 5 students, it can be seen that students' mathematical solving abilities when solving SPLDV story problems are still weak. Story questions about solving mathematical problems can help students think at a high level and be able to solve problems by following the steps given. Therefore, students still need exercises to understand the material and be able to solve problems related to solving these mathematical problems.